Gaps in the relationship of science and technology with economy - a comparison between developed and developing countries - Chi, Hoang Lan (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2017)
The gap in the relationship of science and technology (S&T) with economy compared between developed and developing countries is determined by the level of S&T development in industrialization, technology generation, development wave, technological development level,… From these metrics, some basic characteristics of the gap can be clearly observed in many different aspects along the time, between developed and developing countries, among developing countries themselves, between the regions in a country in respect of the interaction and difference of the gap in the linkage between S&T with economy, scientific and technological gap, economic gap. Gaps in the linkage of S&T with economy compared between developed and developing countries exists in a fairly sustainable way for many different reasons, such as internal limitation of developing countries, obstacles in dissemination of S&T achievements, intention of developed countries,… Analysis of characteristics and causes of the gap in the relationship of S&T and economy compared between developed and developing countries is a meaningful study to provide basis for finding out solutions to reduce this gap.